The Emerging Global Order: A Comparative Analysis of China and US Strategies in the Indo-Pacific Region - Ahsan Saeed; Aliza Shahzad; Sabeen Malik, (ASIAN Journal of International Peace & Security (AJIPS), 2025)
This research aims to compare and analyze the strategies of China and the United States in the Indo-Pacific region with respect to emerging global order. The research employs qualitative research method and thematic analysis to comparatively analyze the strategies of these great powers. The research examines these policies through two contrasting theoretical frameworks. First, Offensive Realism to analyze the US strategy. Second, the English School of Thought to understand China’s approach in the IndoPacific Region. The study argues that the world order is shifting from Pax-Americana to Pax-Sinica. The new world order will be multipolar in nature, where the US will remain the dominant power but not unilaterally, other powers, will join hands in shaping the geopolitical and geo-economic affairs. China is expected to assume the leading role in geo-economic affairs. Rather than dismantling the liberal institutional order, China will refine the existing framework by introducing Chinese characteristics of “shared destiny” or win-win cooperation and avoid confrontation or intervention in domestic affairs. Pax-Sinica order will be focused on geo-economics and will not pay attention to the internal political dynamics of any sovereign country. Hence, the liberal institutional order will be sustained, however, with a new set of rules and norm.